Statistical Programs In The Teaching Of Physical Education Classes - et. al., Yakhshieva Mekhrinigor, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The scientific work is devoted to the analysis and application of applied statistical programs in teaching the discipline "Sports metrology". The state conducts a comparative analysis of statistical software packages and their capabilities, shows the role of sports metrology and methods of mathematical statistics, as well as mathematical analysis, which are a powerful help in the scientific approach to the development of sports, where physical education and sports training of female students are a kind of production process, a product which is the physical, technical, tactical, psychological and theoretical readiness of the trainees (and in general for the athletes - their sports readiness). The use of the methods of mathematical statistics makes it possible to conduct an objective analysis of the results of pedagogical, medical, psychological examinations and obtain substantiated recommendations for improving sports training. A comparison of various statistical programs is given, where it should be borne in mind that almost all of them have a set of standard procedures.